2007
DOI: 10.1002/bip.20790
|View full text |Cite
|
Sign up to set email alerts
|

Sequence specificity of inter‐ and intramolecular G‐quadruplex formation by human telomeric DNA

Abstract: Human telomeric DNA consists of tandem repeats of the sequence 5'-d(TTAGGG)-3'. Guanine-rich DNA, such as that seen at telomeres, forms G-quadruplex secondary structures. Alternative forms of G-quadruplex structures can have differential effects on activities involved in telomere maintenance. With this in mind, we analyzed the effect of sequence and length of human telomeric DNA on G-quadruplex structures by native polyacrylamide gel electrophoresis and circular dichroism. Telomeric oligonucleotides shorter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 38 publications
10
69
0
Order By: Relevance
“…Although there are examples to support this relationship for intramolecular G quadruplexes as well (Matsugami et al 2001(Matsugami et al , 2003Seenisamy et al 2004;Ambrus et al 2005), a generalization cannot be made since there are not enough intramolecular parallel type I highresolution G quadruplex structures available. In addition to the positive band around 265 nm and the negative one around 240 nm, the CD spectrum of MAP1B RNA shows a positive shoulder around 290 nm, spectral features that have been previously reported for intramolecular G-quadruplexes with anti-glycosidic bonds and external or ''propeller'' loops (Xu et al 2006;Pedroso et al 2007). …”
Section: Resultssupporting
confidence: 67%
“…Although there are examples to support this relationship for intramolecular G quadruplexes as well (Matsugami et al 2001(Matsugami et al , 2003Seenisamy et al 2004;Ambrus et al 2005), a generalization cannot be made since there are not enough intramolecular parallel type I highresolution G quadruplex structures available. In addition to the positive band around 265 nm and the negative one around 240 nm, the CD spectrum of MAP1B RNA shows a positive shoulder around 290 nm, spectral features that have been previously reported for intramolecular G-quadruplexes with anti-glycosidic bonds and external or ''propeller'' loops (Xu et al 2006;Pedroso et al 2007). …”
Section: Resultssupporting
confidence: 67%
“…1I, arrows). These products were similar to faster and slower migrating G-quadruplex species reported for telomere oligonucleotides with varying repeat numbers (22). The formation of additional and distinct electrophoretic species is consistent with the formation of uni-and multimolecular G-quadruplexes with increasing repeat length (Fig.…”
Section: Ion Dependence Of the Slow Migrating R(ggggcc)supporting
confidence: 66%
“…Increasing repeat numbers can affect G-quadruplex formation by telomere repeats and slipped DNAs and R-loops by (CAG)/ (CTG) and (CGG)/(CCG) repeats (22)(23)(24)(25)(26). Here we analyzed increasing r(GGGGCC) n repeat lengths of n ϭ 4, 6, and 8 units (Fig.…”
Section: Ion Dependence Of the Slow Migrating R(ggggcc)mentioning
confidence: 99%
“…G3 formed a mixed parallel/antiparallel quadruplex in potassium phosphate buffer but remained unstructured when annealed in neat water, which is consistent with the data existing in the literature. 3 When annealed in the presence of an equimolar amount of PNA 1, G3 formed a mixed parallel/antiparallel quadruplex in potassium phosphate buffer but also in neat water, which is consistent with the UV melting experiments demonstrating that PNA 1 could induce the formation of a quadruplex even under conditions where the dimeric DNA quadruplex cannot form. Interestingly, (i) the absolute amount of quadruplex formed decreased when decreasing the salt concentration, (ii) the 260/295 CD ratio remains almost constant for either the G3 or for the G3/PNA 1 complex whatever the buffer and (iii) the 260/295 ratio remains significantly higher for the PNA/DNA quadruplex than for the pure DNA quadruplex.…”
Section: Resultssupporting
confidence: 83%
“…1 Converging in silico and in vitro data have revealed the high prevalence of such Grich DNA sequences throughout the human genome.P 2 PR ecently there has been considerable focus on quadruplexes, their cellular functions, and their exploitation for biological intervention towards therapeutics. The most widely studied DNA quadruplexes are those derived from telomeric repeat sequences.P [3][4][5][6] P Biophysical studies on the human telomeric quadruplex have provided valuable insights into its structural and dynamic properties.P 3 P NMR and X-ray crystal structures of the intramolecular quadruplex formed from four human telomeric repeats (GGGTTA) have revealed that it is highly polymorphic.P 4 PS everal lines of evidence link G-quadruplexes with telomere maintenanceP 5 P given that telomeric DNA in its quadruplex form is not a competent substrate for telomerase.P 6 P Telomerase is crucial for immortality in most human cancers and therefore ligand induced quadruplex stabilisation in telomeric DNA has potential as an anti-cancer therapeutic strategy.P An original approach was also recently reported that uses an anthracene-diethylene triamine conjugate to induce intramolecular parallel quadruplex formation from singlestranded DNA via stacking of the anthracene moiety onto the external G-tetard and invasion of the central ion channel by the triamine side-chain. 11 Peptide Nucleic Acid (PNA) is a synthetic mimic of DNA in which the negatively charged phosphate backbone is replaced by a neutral polyamide backbone, thus allowing it to hybridise in a sequence specific manner and with high affinity to either DNA or RNA.…”
Section: Introductionmentioning
confidence: 99%